Biological ceramic microsphere soft tissue injection as well as preparation method and application thereof

By preparing soft tissue injections composed of bioceramic microspheres with smooth pores on the surface and gel carrier, the problem of high inflammatory response in soft tissue filling of existing bioceramic materials is solved, low immunogenicity and good biocompatibility are achieved, and collagen regeneration is promoted.

CN120501927AActive Publication Date: 2025-08-19YANTAI ZHENGHAI BIO TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510660895.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2025-08-19
Estimated Expiration
2045-05-22

AI Technical Summary

Technical Problem

Existing bioceramic materials have problems with high inflammatory response and poor biocompatibility in soft tissue filling, especially high pH caused by silicate materials may lead to severe inflammation.

Method used

Using soft tissue injection composed of bioceramic microspheres and gel carriers, the bioceramic microspheres are prepared by spray drying. The surface is smooth and porous, with particle sizes of 20μm to 50μm, and contain calcium, phosphorus, silicon, and magnesium active elements to reduce the inflammatory response.

Benefits of technology

Bioceramic microspheres are prone to flow into soft tissues when injected, providing growth scaffolds, reducing immune responses, having good biocompatibility and biological activity, promoting collagen regeneration, and reducing inflammatory responses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120501927A_ABST
    Figure CN120501927A_ABST
Patent Text Reader

Abstract

The invention discloses a biological ceramic microsphere soft tissue injection as well as a preparation method and application thereof, and relates to the technical field of biomedical materials. Comprising the following raw materials in parts by weight: 100-120 parts of a gel carrier and 50-98 parts of biological ceramic microspheres. The invention designs a biological ceramic microsphere soft tissue injection, the soft tissue injection is composed of biological ceramic microspheres and a gel carrier, and the biological ceramic microspheres used in the invention reduce inflammatory response of the biological ceramic microsphere soft tissue injection while ensuring good cell viability, loading capacity and rheological property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a bioceramic microsphere soft tissue injection, a preparation method and an application thereof. Background Art

[0002] Since the latter half of the 20th century, the pursuit of facial rejuvenation has become a popular trend. Injection plastic surgery has gained widespread popularity due to its ease of use, minimal trauma, high safety, short recovery period, and remarkable results. This technique not only satisfies people's pursuit of beauty but also rapidly becomes a popular choice in the market due to its rapid effectiveness. With the continuous advancement of technology and the growing pursuit of beauty, the market demand for injection plastic surgery has seen explosive growth, becoming one of the preferred cosmetic procedures for many beauty-conscious individuals. In the field of medical cosmetic injections, the mainstream filler materials currently used are primarily non-autologous tissue injectables. These materials include not only simple ingredients like hyaluronic acid (HA) and collagen, but also composite fillers that stimulate collagen and fiber production, such as polycaprolactone (PCL), poly-L-lactic acid (PLLA), and calcium hydroxyapatite (CaHA). These advanced materials have begun to be used clinically and are gradually gaining a foothold in the injectable micro-plastic surgery market. However, hyaluronic acid is easily degraded by enzymes in the body, so its retention time is short, providing only a temporary volume filling effect. To maintain the desired cosmetic effect, regular injections are required. However, excessive injection of hyaluronic acid or its cross-linked form can easily cause excessive facial swelling and the appearance of a swelled face due to its high water absorption and swelling properties. PLLA or PCL, as injectable filler materials, while having the advantage of stimulating collagen production, may cause adverse reactions such as local bruising, pain, hematoma, local inflammatory reactions, and edema that may last for 3 to 5 days. Hydroxyapatite, as a naturally occurring material in human tissue, has excellent biocompatibility and can effectively fill and repair soft tissues, thereby providing appropriate structural support and maintaining the volume and shape after injection.

[0003] Chinese patent CN 110292655A discloses an injectable filling preparation containing hydroxyapatite and its preparation method, and evaluates the wrinkle-removing effect of hydroxyapatite in soft tissue filling through clinical trials.

[0004] Chinese patent CN 117982735A discloses an antibacterial injectable cosmetic filler and its preparation method. Hydroxyapatite microspheres are prepared by an oil phase reaction method and mixed with collagen paste. The microspheres are then implanted subcutaneously in rabbits and exhibit good filling effects.

[0005] To reduce foreign body irritation and inflammatory responses, hydroxyapatite is typically fabricated in the form of microspheres. Because hydroxyapatite is insoluble in water or organic solvents, it is difficult to prepare microspheres using methods such as emulsion polymerization, membrane emulsification, and microfluidics. However, microspheres can be prepared using hydrothermal methods, spray drying, sol-gel methods, and template methods. Spray drying offers advantages such as stable microsphere structure, uniform particle size, and reproducible results, making it amenable to industrial large-scale production.

[0006] However, due to the relative inertness of hydroxyapatite, it is not ideal in promoting collagen secretion. Doping silicon and magnesium elements on the basis of hydroxyapatite can obtain calcium magnesium-based silicon phosphate bioceramics, which have excellent biological activity compared with hydroxyapatite and can release Ca during degradation. 2+ 、Si 4+ Mg 2+ Various ion products, such as silicate phosphates, significantly promote vascularization and tissue regeneration, leading to excellent collagen regeneration and long-lasting filling effects. Similarly, Chinese patent CN116672496A discloses an injectable tissue filler containing silicate ceramic microspheres, its preparation method, and application. The silicate ceramic microspheres, prepared via a sol-spray method, can provide excellent filling. However, silicophosphate bioceramics have a high pH and can cause localized elevated pH, leading to severe inflammatory reactions, making them unsuitable for direct use as fillers.

[0007] Therefore, how to reduce the inflammatory response caused by silicate materials and improve biocompatibility is of great significance to improving the safety of bioceramic materials. Summary of the Invention

[0008] In response to the shortcomings of the prior art, the present invention has designed a bioceramic microsphere soft tissue injection, which is composed of bioceramic microspheres and a gel carrier. The bioceramic microspheres used in the present invention not only ensure good cell activity, loading capacity, and rheological properties, but also reduce the inflammatory response of the bioceramic microsphere soft tissue injection, thereby solving the technical problems raised in the background art. Specifically, the technical solution of the present invention includes the following:

[0009] A bioceramic microsphere soft tissue injection, comprising the following raw materials in parts by weight:

[0010] 100-120 parts by weight of gel carrier and 90-98 parts by weight of bioceramic microspheres.

[0011] Furthermore, the preparation method of the gel carrier comprises the following steps:

[0012] 110-120 parts by weight of purified water and 2-3 parts by weight of biomacromolecule material are mixed and mechanically stirred to form a gel carrier.

[0013] Furthermore, the purified water can also be replaced with sterile water or deionized water.

[0014] Furthermore, the conditions for the mechanical stirring include a stirring temperature of 25° C. to 30° C., a stirring speed of 200 r / min to 300 r / min, and a stirring time of 30 min to 40 min.

[0015] Furthermore, the biomacromolecule material includes sodium hyaluronate, and may also be sodium carboxymethyl cellulose, collagen or gelatin.

[0016] Furthermore, the preparation method of the bioceramic microspheres comprises the following steps:

[0017] 95 to 150 parts by weight of calcium phosphate and 95 to 105 parts by weight of silicate are mixed and ball-milled to obtain ceramic powder;

[0018] 190 to 200 parts by weight of ceramic powder, 4.5 to 5.0 parts by weight of binder, 0 to 3.5 parts by weight of wetting agent and 500 parts by weight of purified water are mixed to form a spray slurry;

[0019] The spray slurry is spray granulated at 200° C. to 260° C. to form a bioceramic microsphere green body;

[0020] The bioceramic microsphere green body is sintered at 1100° C. to 1400° C. for 1 to 2 hours and then sieved to obtain the bioceramic microsphere.

[0021] Furthermore, the calcium phosphate is selected from any one or both of hydroxyapatite and β-tricalcium phosphate, and the calcium phosphate can also be selected from α-tricalcium phosphate or tetracalcium phosphate.

[0022] Furthermore, the silicate includes white wellstone, and siliceous apatite, bioglass or wollastonite may also be used.

[0023] Furthermore, the conditions for the mixed ball milling include a ball milling temperature of 25° C. to 30° C., a ball milling speed of 300 r / min to 400 r / min, and a ball milling time of 2 h to 4 h.

[0024] Furthermore, the adhesive includes polyvinyl alcohol or polyvinyl pyrrolidone.

[0025] Furthermore, the wetting agent includes polysorbate 80 or polysorbate 60.

[0026] Furthermore, the particle size range of the screening is 20μm to 50μm.

[0027] A method for preparing a bioceramic microsphere soft tissue injection, the method comprising the following steps:

[0028] The gel carrier and bioceramic microspheres were mixed and homogenized under high pressure, then loaded into a syringe and sterilized under high pressure at 121° C. for 30 minutes to obtain a bioceramic microsphere soft tissue injection.

[0029] Furthermore, the conditions for the high-pressure homogenization include a homogenization pressure of 10 MPa to 20 MPa, a homogenization speed of 1000 r / min to 1800 r / min, and a homogenization time of 8 min to 10 min.

[0030] Application of a bioceramic microsphere soft tissue injection in the field of collagen regeneration.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The bioceramic microspheres prepared in the present invention are spherical and have a smooth surface. The smooth spherical shape makes it easier for the bioceramic microspheres to pass through the syringe during injection and can flow into the soft tissue area to be filled with a lower thrust force.

[0033] (2) The bioceramic surface prepared by the present invention has pores. These pores increase the contact area between the bioceramic microspheres and the gel, increasing friction and helping to keep the microspheres suspended in the gel. Once these microspheres reach the target tissue site, they provide a scaffold for the growth of autologous tissue.

[0034] (3) The ideal size of the microspheres prepared in the present invention is between 20 μm and 50 μm, which is not only convenient for injection but also can minimize the microspheres from being taken up by macrophages and provoking immune inflammatory responses.

[0035] (4) The bioceramic microspheres used in the present invention are calcium phosphate or magnesium silicate, containing active elements of calcium, phosphorus, silicon, and magnesium, and have good biocompatibility and bioactivity. After being injected into soft tissue, they have low immunogenicity and rarely cause severe inflammatory reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 These are SEM images of bioceramic microspheres prepared in Preparation Example 5 of the present invention, where the scale in (A) is 100 μm and the scale in (B) is 10 μm;

[0037] Figure 2 These are SEM images of bioceramic microspheres prepared in Preparation Example 6 of the present invention, where the scale in (A) is 100 μm and the scale in (B) is 10 μm;

[0038] Figure 3 These are SEM images of the bioceramic microspheres prepared in Preparation Example 7 of the present invention, where the scale in (A) is 100 μm and the scale in (B) is 10 μm;

[0039] Figure 4 This is an SEM image of the bioceramic microspheres prepared in Preparation Example 13 of the present invention. The scale in the figure is 20 μm.

[0040] Figure 5 The cell proliferation activity results of the bioceramic microspheres prepared in Preparation Examples 5 to 7 and Preparation Examples 8 to 10 of the present invention;

[0041] Figure 6 The rheological properties of the bioceramic microsphere soft tissue injection prepared in Example 3 of the present invention and Comparative Example 1, wherein G' represents the storage modulus, G" represents the loss modulus, and η represents the viscosity;

[0042] Figure 7 Results of H&E staining of samples from the implantation sites of the bioceramic microsphere soft tissue injections prepared in Example 3 and Comparative Example 2, 2 weeks after implantation in rabbits;

[0043] Figure 8 The results of Sirius red staining of the implantation site samples after the bioceramic microsphere soft tissue injection prepared in Example 3 and Comparative Example 2 was implanted into rabbits. DETAILED DESCRIPTION

[0044] The following will clearly and completely describe the technical solutions of the present invention through the embodiments and drawings of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making any creative efforts shall fall within the scope of protection of the present invention.

[0045] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0046] Preparation Example 1

[0047] The preparation method of the gel carrier specifically includes the following steps:

[0048] 0.15 g of sodium hyaluronate was slowly added to 120 g of purified water and mixed, and then placed in a temperature environment of 25° C. and mechanically stirred for 30 minutes by a stirring blade at a speed of 200 r / min to complete the preparation of the gel carrier.

[0049] Preparation Example 2

[0050] The preparation method of the gel carrier specifically includes the following steps:

[0051] 4.6 g of sodium hyaluronate was slowly added to 110 g of purified water and mixed, and then placed in a temperature environment of 25° C. and mechanically stirred for 35 minutes by a stirring blade at a speed of 250 r / min to complete the preparation of the gel carrier.

[0052] Preparation Example 3

[0053] The preparation method of the gel carrier specifically includes the following steps:

[0054] 3 g of sodium hyaluronate was slowly added to 120 g of purified water and mixed, and then placed in a temperature environment of 30° C. and mechanically stirred for 40 minutes by a stirring blade at a speed of 300 r / min to complete the preparation of the gel carrier.

[0055] Preparation Example 4

[0056] The preparation method of the gel carrier specifically includes the following steps:

[0057] 10 g of sodium hyaluronate was slowly added to 120 g of purified water and mixed, and then placed in a temperature environment of 30° C. and mechanically stirred for 40 minutes by a stirring blade at a speed of 300 r / min to complete the preparation of the gel carrier.

[0058] Preparation Example 5

[0059] The preparation method of bioceramic microspheres specifically includes the following steps:

[0060] Weigh 95 g of hydroxyapatite and 95 g of choriasite, mix them evenly, put them into a ball mill, and grind them at a speed of 300 r / min for 4 h in an environment of 25°C to obtain ceramic powder;

[0061] Weigh 190g of ceramic powder, 4.5g of polyvinyl pyrrolidone, and 500g of purified water and mix them evenly to prepare a spray slurry;

[0062] The spray slurry is fed into a spray dryer and spray granulated at a temperature of 200° C. to obtain bioceramic microsphere green bodies;

[0063] The bioceramic microspheres were placed in a high temperature environment of 1400℃ for 1 hour. After sintering, they were naturally cooled to room temperature and sieved to obtain bioceramic microspheres with a particle size range of 20 to 50 μm. The bioceramic microspheres were characterized by scanning electron microscopy. Figure 1 As shown, the bioceramic microspheres have a relatively smooth surface and certain pores.

[0064] Preparation Example 6

[0065] The preparation method of bioceramic microspheres specifically includes the following steps:

[0066] Weigh 65 g of hydroxyapatite, 65 g of β-tricalcium phosphate, and 100 g of white wellstone, mix them evenly, put them into a ball mill, and grind them at 350 r / min in an environment of 25°C for 3 h to obtain ceramic powder;

[0067] Weigh 195 g of ceramic powder, 4.7 g of polyvinyl alcohol, 3.5 g of polysorbate 80, and 500 g of purified water and mix them evenly to prepare a spray slurry;

[0068] The spray slurry is fed into a spray dryer and spray granulated at a temperature of 240° C. to obtain bioceramic microsphere green bodies;

[0069] The bioceramic microspheres were placed in a high temperature environment of 1100℃ and sintered for 2 hours. After sintering, they were naturally cooled to room temperature and sieved to obtain bioceramic microspheres with a particle size range of 20 to 50 μm. The bioceramic microspheres were characterized by scanning electron microscopy. Figure 2 As shown, the bioceramic microspheres have a relatively smooth surface and certain pores.

[0070] Preparation Example 7

[0071] The preparation method of bioceramic microspheres specifically includes the following steps:

[0072] Weigh 150 g of β-tricalcium phosphate and 105 g of white wellstone, mix them evenly, put them into a ball mill, and grind them at 400 r / min in an environment of 30°C for 2 h to obtain ceramic powder;

[0073] Weigh 200 g of ceramic powder, 5.0 g of polyvinyl pyrrolidone, 2 g of polysorbate 60, and 500 g of water and mix them evenly to prepare a spray slurry;

[0074] The spray slurry is fed into a spray dryer and spray granulated at a temperature of 260° C. to obtain bioceramic microsphere green bodies;

[0075] The bioceramic microspheres were placed in a high temperature environment of 1250℃ for 1 hour. After sintering, they were naturally cooled to room temperature and sieved to obtain bioceramic microspheres with a particle size range of 20 to 50 μm. The bioceramic microspheres were characterized by scanning electron microscopy. Figure 3 As shown, the bioceramic microspheres have a relatively smooth surface and certain pores.

[0076] Preparation Example 8

[0077] The preparation method of bioceramic microspheres specifically includes the following steps:

[0078] Weigh 200 g of hydroxyapatite nanopowder directly as ceramic powder, 5.0 g of polyvinyl pyrrolidone, 2 g of polysorbate 60 and 500 g of water and mix them evenly to prepare a spray slurry;

[0079] The spray slurry is fed into a spray dryer and spray granulated at a temperature of 260° C. to obtain bioceramic microsphere green bodies;

[0080] The bioceramic microsphere green body was placed in a high temperature environment of 1250° C. and sintered for 1 hour. After the sintering was completed, it was naturally cooled to room temperature and sieved to obtain bioceramic microspheres with a particle size range of 20 to 50 μm.

[0081] Preparation Example 9

[0082] The preparation method of bioceramic microspheres specifically includes the following steps:

[0083] Weigh 200 g of magnesia nanopowder directly as ceramic powder, 5.0 g of polyvinyl pyrrolidone, 2 g of polysorbate 60 and 500 g of water and mix them evenly to prepare a spray slurry;

[0084] The spray slurry is fed into a spray dryer and spray granulated at a temperature of 260° C. to obtain bioceramic microsphere green bodies;

[0085] The bioceramic microsphere green body was placed in a high temperature environment of 1250° C. and sintered for 1 hour. After the sintering was completed, it was naturally cooled to room temperature and sieved to obtain bioceramic microspheres with a particle size range of 20 to 50 μm.

[0086] Preparation Example 10

[0087] The preparation method of bioceramic microspheres specifically includes the following steps:

[0088] Weigh 255 g of calcium silicate powder and mix them evenly, then put them into a ball mill and grind them at 400 rpm for 2 h at 30°C to obtain ceramic powder.

[0089] Weigh 200 g of ceramic powder, 5.0 g of polyvinyl pyrrolidone, 2 g of polysorbate 60, and 500 g of water and mix them evenly to prepare a spray slurry;

[0090] The spray slurry is fed into a spray dryer and spray granulated at a temperature of 260° C. to obtain bioceramic microsphere green bodies;

[0091] The bioceramic microspheres were placed in a high temperature environment of 1250°C for 1 hour, and then naturally cooled to room temperature after sintering and sieved to obtain bioceramic microspheres with a particle size range of 20 to 50 μm.

[0092] Preparation Example 11

[0093] The preparation method of bioceramic microspheres specifically includes the following steps:

[0094] Weigh 50 g of β-tricalcium phosphate and 150 g of white wellstone, mix them evenly, put them into a ball mill, and grind them at 400 r / min in an environment of 30°C for 2 h to obtain ceramic powder;

[0095] Weigh 200 g of ceramic powder, 5.0 g of polyvinyl pyrrolidone, 2 g of polysorbate 60, and 500 g of water and mix them evenly to prepare a spray slurry;

[0096] The spray slurry is fed into a spray dryer and spray granulated at a temperature of 260° C. to obtain bioceramic microsphere green bodies;

[0097] The bioceramic microspheres were placed in a high temperature environment of 1250°C for 1 hour, and then naturally cooled to room temperature after sintering and sieved to obtain bioceramic microspheres with a particle size range of 20 to 50 μm.

[0098] Preparation Example 12

[0099] The preparation method of bioceramic microspheres specifically includes the following steps:

[0100] Weigh 150 g of β-tricalcium phosphate and 105 g of white wellstone, mix them evenly, put them into a ball mill, and grind them at 400 r / min in an environment of 30°C for 2 h to obtain ceramic powder;

[0101] Weigh 200 g of ceramic powder, 5.0 g of polyvinyl pyrrolidone, 2 g of polysorbate 60, and 500 g of water and mix them evenly to prepare a spray slurry;

[0102] The spray slurry is fed into a spray dryer and spray granulated at a temperature of 260° C. to obtain bioceramic microsphere green bodies;

[0103] The bioceramic microsphere green body was placed in a high temperature environment of 1000°C for 1 hour. After sintering, it was naturally cooled to room temperature and sieved to obtain bioceramic microspheres with a particle size range of 20 to 50 μm.

[0104] Preparation Example 13

[0105] The preparation method of bioceramic microspheres specifically includes the following steps:

[0106] Weigh 150 g of β-tricalcium phosphate and 105 g of white wellstone, mix them evenly, put them into a ball mill, and grind them at 400 r / min in an environment of 30°C for 2 h to obtain ceramic powder;

[0107] Weigh 200 g of ceramic powder, 5.0 g of polyvinyl pyrrolidone, 2 g of polysorbate 60, and 500 g of water and mix them evenly to prepare a spray slurry;

[0108] The spray slurry is fed into a spray dryer and spray granulated at a temperature of 260° C. to obtain bioceramic microsphere green bodies;

[0109] The bioceramic microspheres were placed in a high temperature environment of 1500℃ and sintered for 2h. After sintering, they were naturally cooled to room temperature and sieved to obtain bioceramic microspheres with a particle size range of 20 to 50μm. The bioceramic microspheres were characterized by scanning electron microscopy. The results are as follows: Figure 4 As shown, the microspheres melted and adhered severely.

[0110] (1) Verification of the cell activity of the bioceramic microspheres obtained in Preparation Examples 5 to 13:

[0111] The cell activity of the bioceramic microspheres prepared in Examples 5 to 13 was evaluated by the CCK-8 method. Human fibroblasts (MRC5) were inoculated on the surface of the bioceramic microspheres prepared in Examples 5 to 13, and the cell proliferation rate was tested by absorbance on the 1st, 3rd, 5th and 7th day. The results are as follows: Figure 5 shown.

[0112] pass Figure 5 It can be found that the cell proliferation rate of the bioceramic microspheres prepared in Preparation Examples 5 to 7 is significantly better than that of Preparation Examples 8 to 13, indicating that the bioceramic microspheres prepared in Preparation Examples 5 to 7 have better biocompatibility. Compared with the bioceramic microspheres prepared by single hydroxyapatite, magnesia feldspar, or calcium silicate, the bioceramic microspheres prepared by the composite action of calcium phosphate and silicate in Preparation Examples 5 to 7 may have a richer and more balanced ion release capacity containing calcium, phosphorus, silicon, magnesium, etc., which is conducive to the adhesion, migration and ingrowth of local repair cells and new tissues, thereby promoting a cell proliferation rate much higher than that of the bioceramic microspheres obtained in Preparation Examples 8 to 10. Through Preparation Example 11 and Preparation Example 7, it can be found that when the amount of β-tricalcium phosphate is reduced and the amount of white assemblage is increased, the cell proliferation rate of the bioceramic microspheres prepared in Preparation Example 11 is significantly worse. By comparing Preparation Examples 12 and 13 with Preparation Example 7, it can be found that in this system, the cell proliferation rate of the bioceramic microspheres prepared in Preparation Examples 12 and 13 is poor. This may be because the raw materials used in the preparation of bioceramic microspheres in this system have certain requirements for the calcination temperature. If the temperature exceeds a certain range, the activity of the bioceramic microspheres may be affected due to insufficient or excessive calcination. This shows that the raw materials, ratios, and calcination conditions of the bioceramic microspheres prepared by the present invention have an important influence on the bioceramic microspheres, and not all ratios can produce bioceramic microspheres with good cell activity according to the system of the present invention.

[0113] (2) Testing the maximum load, pH, and pushing force of the bioceramic microspheres prepared in Preparation Examples 5 to 13:

[0114] Prepare six homogenizer mixing tanks, numbered ① to 9, and add 113.52 g of the gel carrier obtained in Preparation Example 3 to each of the nine mixing tanks;

[0115] Next, 1 g of the bioceramic microspheres obtained in Preparation Example 5 was added to Tank 1, which was then placed in a homogenizer. The homogenization pressure was controlled at 20 MPa and the homogenization speed was controlled at 1800 r / min for high-pressure homogenization. Subsequently, 1 g of the bioceramic microspheres obtained in Preparation Example 5 was added in small amounts and multiple times during the homogenization process until particles and hard lumps appeared in the gel in Tank 1. The cumulative amount of bioceramic microspheres obtained in Preparation Example 5 added was recorded.

[0116] Similarly, the preparation examples 6 to 13 were dispersed into mixing tanks ② to 9 respectively according to the above method, and the cumulative addition amount of the bioceramic microspheres obtained in the preparation examples 6 to 13 was recorded respectively;

[0117] Finally, the maximum load of the bioceramic microspheres obtained in Preparation Examples 5 to 13 was calculated, and the pH was tested using a pH meter, and the pushing force was tested using a universal testing machine at a speed of 30 mm / min. The test results are shown in Table 1.

[0118] Table 1 Comparison of maximum load, pH and pushing force

[0119]

[0120]

[0121] *Note: “ / ” in Table 1 means that the needle could not be squeezed out or burst during the test, so no data could be measured.

[0122] It can be seen from Table 1 that Preparation Examples 5 to 7 maintain a lower pushing force while achieving a higher microsphere loading. It is not difficult to see from the table that as the composition of the microspheres changes, their pH also changes significantly. The pH of Preparation Examples 5 to 7 is all below 8, which are neutral or weakly alkaline; the pH of Preparation Examples 8 to 12 is above 8, which is alkaline. Sodium hyaluronate will be completely ionized in an alkaline environment with high pH, resulting in an increase in the ionic strength of the solution, thereby reducing the flexibility of the molecular chain and the viscosity of the solution. This change makes the microspheres easier to settle and difficult to form a stable suspension state in the gel carrier; although Preparation Example 13 has a pH close to neutral, the sintering temperature is too high, which causes the microspheres to melt and have severe adhesion, which can be explained by Figure 4As can be seen from the SEM images, extrusion is extremely difficult. This is likely due to the selective requirements for the raw materials, raw material ratios, and sintering temperature used in the preparation of bioceramic microspheres in this system. The low extrusion force and high microsphere loading improve the convenience of the injection in clinical practice and help prolong the duration of collagen regeneration and repair effects.

[0123] Example 1

[0124] A method for preparing a bioceramic microsphere soft tissue injection specifically includes the following steps:

[0125] Weigh 50 g of the bioceramic microspheres obtained in Preparation Example 5 and slowly add them to 120 g of the gel carrier obtained in Preparation Example 1 to mix. Then put them into a homogenizer, control the homogenization pressure to 10 MPa and the homogenization speed to 1000 r / min, and perform high-pressure homogenization for 8 minutes to fully disperse the bioceramic microspheres in the gel carrier. After the homogenization treatment, the obtained composite material is loaded into a 1.5 mL syringe and then sterilized in a high-pressure sterilizer at 121°C for 30 minutes to obtain a bioceramic microsphere soft tissue injection, and its pushing force is tested.

[0126] Example 2

[0127] A method for preparing a bioceramic microsphere soft tissue injection specifically includes the following steps:

[0128] Weigh 98 g of the bioceramic microspheres obtained in Preparation Example 6 and slowly add them to 100 g of the gel carrier obtained in Preparation Example 2 to mix. Then put them into a homogenizer, control the homogenization pressure to 15 MPa and the homogenization speed to 1300 r / min, and perform high-pressure homogenization for 9 minutes to fully disperse the bioceramic microspheres in the gel carrier. After the homogenization treatment, the obtained composite material is loaded into a 1.5 mL syringe and then sterilized in a high-pressure sterilizer at 121°C for 30 minutes to obtain a bioceramic microsphere soft tissue injection, and its pushing force is tested.

[0129] Example 3

[0130] A method for preparing a bioceramic microsphere soft tissue injection specifically includes the following steps:

[0131] Weigh 98 g of the bioceramic microspheres obtained in Preparation Example 7 and slowly add them to 120 g of the gel carrier obtained in Preparation Example 3 to mix. Then put them into a homogenizer, control the homogenization pressure to 20 MPa and the homogenization speed to 1800 r / min, and perform high-pressure homogenization for 10 minutes to fully disperse the bioceramic microspheres in the gel carrier. After the homogenization treatment, the obtained composite material is loaded into a 1.5 mL syringe and then sterilized in a high-pressure sterilizer at 121°C for 30 minutes to obtain a bioceramic microsphere soft tissue injection, and its pushing force is tested.

[0132] Comparative Example 1

[0133] A method for preparing a bioceramic microsphere soft tissue injection specifically includes the following steps:

[0134] Weigh 98 g of the bioceramic microspheres obtained in Preparation Example 7 and slowly add them to 120 g of the gel carrier obtained in Preparation Example 4 to mix. Then put them into a homogenizer, control the homogenization pressure to 20 MPa and the homogenization speed to 1800 r / min, and perform high-pressure homogenization for 10 minutes to fully disperse the bioceramic microspheres in the gel carrier. After the homogenization treatment, the obtained composite material is loaded into a 1.5 mL syringe and then sterilized in a high-pressure sterilizer at 121°C for 30 minutes to obtain a bioceramic microsphere soft tissue injection, and its pushing force is tested.

[0135] Comparative Example 2

[0136] A method for preparing a bioceramic microsphere soft tissue injection specifically includes the following steps:

[0137] 30 g of the bioceramic microspheres obtained in Preparation Example 7 were weighed and slowly added to 125 g of the gel carrier obtained in Preparation Example 3 and mixed. The mixture was then placed in a homogenizer, the homogenization pressure was controlled to 20 MPa, the homogenization speed was controlled to 1800 r / min, and the high-pressure homogenization was performed for 10 minutes to fully disperse the bioceramic microspheres in the gel carrier. After the homogenization treatment, the obtained composite material was loaded into a 1.5 mL syringe and then sterilized in a high-pressure sterilizer at 121°C for 30 minutes to obtain a bioceramic microsphere soft tissue injection, and its pushing force was tested.

[0138] Comparative Example 3

[0139] A method for preparing a bioceramic microsphere soft tissue injection specifically includes the following steps:

[0140] 120 g of the bioceramic microspheres obtained in Preparation Example 7 were weighed and slowly added to 80 g of the gel carrier obtained in Preparation Example 3 and mixed. The mixture was then placed in a homogenizer, the homogenization pressure was controlled to 20 MPa, the homogenization speed was controlled to 1800 r / min, and the high-pressure homogenization treatment was performed for 10 minutes to fully disperse the bioceramic microspheres in the gel carrier. After the homogenization treatment, the obtained composite material was loaded into a 1.5 mL syringe and then sterilized in a high-pressure sterilizer at 121°C for 30 minutes to obtain a bioceramic microsphere soft tissue injection, and its pushing force was tested.

[0141] Comparative Example 4

[0142] A method for preparing a bioceramic microsphere soft tissue injection specifically includes the following steps:

[0143] 63.23 g of the bioceramic microspheres obtained in Preparation Example 8 were weighed and slowly added to 154.81 g of the gel carrier obtained in Preparation Example 3 and mixed. The mixture was then placed in a homogenizer, the homogenization pressure was controlled to 20 MPa, the homogenization speed was controlled to 1800 r / min, and the high-pressure homogenization was performed for 10 minutes to fully disperse the bioceramic microspheres in the gel carrier. After the homogenization treatment, the obtained composite material was loaded into a 1.5 mL syringe and then sterilized in a high-pressure sterilizer at 121°C for 30 minutes to obtain a bioceramic microsphere soft tissue injection, and its pushing force was tested.

[0144] The pushing forces obtained in Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 2 below.

[0145] Table 2 Comparison of pushing force

[0146] Sources Pushing force (N) Example 1 20.34 Example 2 37.20 Example 3 30.41 Comparative Example 1 129.12 Comparative Example 2 9.03 Comparative Example 3 109.59 Comparative Example 4 103.26

[0147] Through the comparison results of the pushing force in Table 2, it can be found that in this system, as the content of bioceramic microspheres increases, the pushing force of the injection tends to increase, that is, the higher the load, the more difficult the injection is to extrude. The pushing force of Examples 1-3 is small, and the extrusion is relatively smooth; the material of Comparative Example 1 is hydroxyapatite, and the bioceramic microspheres prepared by this method are difficult to disperse in the gel, which may be due to the excessive amount of biomacromolecules in the gel carrier, so the prepared filler is uneven and difficult to extrude; Comparative Example 2 contains fewer bioceramic microspheres, so the extrusion is smooth, but reducing the amount of bioceramic microspheres is not conducive to the effect of the injection; Comparative Example 3 contains bioceramic microspheres that exceed the ratio provided by the present invention, and the tested pushing force is high and difficult to extrude. Comparative Example 4 uses hydroxyapatite nanopowder directly as ceramic powder to prepare the bioceramic microspheres. The pushing force of the bioceramic microsphere soft tissue injection prepared by Comparative Example 4 is large, which is not suitable for injection use. This may be because in this system, there are certain selectivity requirements for the raw materials and ratios for the preparation of bioceramic microspheres. This indicates that arbitrary changes in the ratio of bioceramic microspheres and gel carriers, and the selection of formula raw materials, will lead to a decrease in the loading capacity of the bioceramic microspheres in the injection, easily increase the viscosity of the injection, and be unfavorable for use.

[0148] (3) Evaluation of rheological properties of soft tissue injections

[0149] The rheological properties of the bioceramic microsphere soft tissue injections obtained in Example 3 and Comparative Example 1 were evaluated using a parallel plate rheometer (Haake Mars 40, Germany). The test involved measuring the rheological properties under applied stress, recording the deformation behavior of the material under constant stress and its recovery under zero stress, and determining the complex modulus by applying oscillatory stress within the viscoelastic range of the soft tissue injection. The viscosity, storage modulus, and loss modulus were measured at a frequency of 1 Hz and an oscillatory force of 100 Pa. The results are shown in Figure 2. Figure 6 , wherein (A) is the rheological property of Example 3, and (B) is the rheological property of Comparative Example 1.

[0150] pass Figure 6 It can be seen that the bioceramic microsphere soft tissue injection prepared in Example 3 exhibits excellent shear-thinning behavior, meaning that the viscosity of the injection decreases significantly with increasing shear rate. This property not only improves the fluidity of the material during injection but also reduces the applied force, making the injection more convenient. Furthermore, G' and G" also reflect the good elasticity and deformation resistance of the bioceramic microsphere soft tissue injection prepared in Example 3, reflecting its ability to partially restore its initial structure after the shear stress is released, thereby better maintaining the stability of the filling shape after injection, and helping to improve the durability and aesthetic effect of the injection. In contrast, the bioceramic microsphere soft tissue injection prepared in Comparative Example 1 exhibits reduced shear-thinning ability and possesses a very high viscosity. While this possesses a stronger load-bearing capacity, it is not conducive to extrusion from the syringe. This demonstrates that, given a fixed bioceramic microsphere loading, the gel carrier ratio has a significant impact on the final bioceramic microsphere soft tissue injection, and not all ratios can achieve good rheological properties.

[0151] (4) Evaluation of collagen regeneration performance of bioceramic microsphere soft tissue injection

[0152] To verify the collagen regeneration performance of the bioceramic microsphere soft tissue injection prepared by the present invention, the bioceramic microsphere soft tissue injection prepared in Example 3 (experimental group) and Comparative Example 2 (control group) were used for subcutaneous implantation in animals to observe the local inflammatory response and collagen regeneration after implantation in rabbits.

[0153] Experimental methods

[0154] 1) General anesthesia was performed using 10% chloral hydrate injected intravenously. The rabbit's back was shaved to prepare the injection area. After the skin was prepared, the experimental animal was placed in the prone position on the operating table.

[0155] 2) Implant the bioceramic microsphere soft tissue injection into the subcutaneous tissue of the rabbit's back using a 27G injection needle;

[0156] 3) After the operation, each animal was housed in a separate cage.

[0157] Experimental observation

[0158] 1) Observe the condition of the subcutaneous filler and local tissue at specific time points after the filler surgery;

[0159] 2) Specimens were collected from the implantation site, fixed with 10% formaldehyde, routinely decalcified, dehydrated, paraffin-embedded, serially sectioned, and then stained with hematoxylin-eosin (H&E) and Sirius red;

[0160] 3) Observe the inflammatory reaction and collagen regeneration around the implantation site under an optical microscope, and observe the collagen type under a polarized light microscope.

[0161] Result evaluation: Figure 7 、 Figure 8 As shown, the bioceramic microsphere soft tissue injection of the experimental group (Example 3) showed good biocompatibility. No obvious inflammatory reaction was found around the material. Only a small amount of macrophages were surrounded, and fibroblasts were formed to form a thin and flat capsule around the microspheres. Furthermore, fibroblasts participated in the regeneration of collagen and showed a significant collagen regeneration effect. Polarized light microscopy results showed that within 2 weeks after injection, the production of type III collagen was mainly promoted; by 2 months, type I collagen began to be produced; by 6 months, a large amount of type I collagen was produced, thereby forming a collagen network structure with good support in the skin. In contrast, the bioceramic microsphere soft tissue injection of the control group (Comparative Example 2) also had good biocompatibility, but the collagen regeneration effect was significantly weaker than that of the experimental group. It can be seen that although reducing the number of bioceramic microspheres can improve the pushing effect of the prepared bioceramic microsphere soft tissue injection, the corresponding therapeutic effect is reduced, which is not conducive to use.

[0162] It can be seen from the above results that the bioceramic microsphere soft tissue injection prepared according to the preparation method provided by the present invention has good biocompatibility and collagen regeneration effect.

[0163] The above-described embodiments and accompanying drawings provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is merely a specific embodiment of the present invention and is not intended to limit the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention, and such changes and modifications fall within the scope of the present invention as claimed.

Claims

1. A bioceramic microsphere soft tissue injection, characterized in that: The bioceramic microsphere soft tissue injection comprises the following raw materials in parts by weight: 100-120 parts by weight of gel carrier and 50-98 parts by weight of bioceramic microspheres.

2. The bioceramic microsphere soft tissue injection according to claim 1, characterized in that: The preparation method of the gel carrier comprises the following steps: 110-120 parts by weight of purified water and 0.15-4.6 parts by weight of biomacromolecule material are mixed and mechanically stirred to form a gel carrier.

3. The bioceramic microsphere soft tissue injection according to claim 2, characterized in that: The biomacromolecule material includes sodium hyaluronate.

4. The bioceramic microsphere soft tissue injection according to claim 1, characterized in that: The preparation method of the bioceramic microspheres comprises the following steps: 95 to 150 parts by weight of calcium phosphate and 95 to 105 parts by weight of silicate are mixed and ball-milled to obtain ceramic powder; 190 to 200 parts by weight of ceramic powder, 4.5 to 5.0 parts by weight of binder, 0 to 3.5 parts by weight of wetting agent and 500 parts by weight of purified water are mixed to form a spray slurry; The spray slurry is spray granulated at 200° C. to 260° C. to form a bioceramic microsphere green body; The bioceramic microsphere green body is sintered at 1100° C. to 1400° C. for 1 to 2 hours and then sieved to obtain the bioceramic microsphere.

5. The bioceramic microsphere soft tissue injection according to claim 4, characterized in that: The calcium phosphate is selected from any one or both of hydroxyapatite and β-tricalcium phosphate.

6. The bioceramic microsphere soft tissue injection according to claim 4, characterized in that: The silicate includes cristobalite.

7. The bioceramic microsphere soft tissue injection according to claim 4, characterized in that: The binder includes polyvinyl alcohol or polyvinyl pyrrolidone.

8. The bioceramic microsphere soft tissue injection according to claim 4, characterized in that: The wetting agent includes polysorbate 80 or polysorbate 60.

9. A method for preparing a bioceramic microsphere soft tissue injection according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: The gel carrier and bioceramic microspheres were mixed and homogenized under high pressure, then loaded into a syringe and sterilized under high pressure at 121° C. for 30 minutes to obtain a bioceramic microsphere soft tissue injection.

10. Use of the bioceramic microsphere soft tissue injection according to any one of claims 1 to 8 or the bioceramic microsphere soft tissue injection prepared by the preparation method according to claim 9 in the field of collagen regeneration.

Citation Information

Patent Citations

  • Hydroxyapatite-containing injection filling preparation and preparation method thereof

    CN110292655A

  • Antibacterial injectable beauty filler and preparation method thereof

    CN117982735A

  • Calcium silicate / hydroxylapatite composite biological ceramic material and preparation method and application thereof

    CN101700415A

  • Bioactive multilayer multiphase ceramic microsphere material and its preparation method and use

    CN103272279A

  • Degradable bioactive porous ceramic material, preparation method and application of degradable bioactive porous ceramic material

    CN105194728A